Serapan Karbon oleh Mangium dan Sengon Berumur Empat Tahun pada Lahan Pascatambang yang Sudah Direklamasi - Munawar, Ali; Wiryono, Wiryono (Jurnal Natur Indonesia, 2014)
Revegetation is an important part of reclamation activities of mined land, partly due to potential CO2 absorption from theatmosphere, particularly through photosynthetic reactions. This research was aimed to calculate the amount of C absorbedby two major fast growing legume species in most reclaimed mined lands in Indonesia, mangium (Acacia mangium) andalbizia (Paraserianthes falcataria) at four years of age. Three tree samples of each species were destructively taken fromthe reclaimed mined land belong to PT Bukit Asam (PERSERO) Tbk, Tanjung Enim, South Sumatra to obtain plant biomassproduction of both above and below ground. The above ground plant biomass was separated into leaf, branches & twigs,and stem. All these components and the below ground biomass (roots) were then weighed for fresh weight determination.About 200 g of these tree components were dried in an oven at 70oC to obtain their dry weights, and then ground into 60mesh diameter for C analysis using wet destruction method of Walkley and Black. The results showed that up to the fourthyear, mangium sequestered C almost double of that sequestered by sengon stands, 21.66 and 10.35 kg C/tree respectively.